EBSD analysis on aluminum brazing sheet for automotive heat exchangers - 纪艳丽 郭富安 沈健生 (Transactions of Nonferrous Metals Society of China, 2006)
Grain boundary character distribution （GBCD） in the vicinity of clad-core interface in annealed aluminum brazing sheet was investigated by EBSD technique. The results show that, with the increase of annealing temperature, the frequency of special boundaries increases, but the random boundary network can not be fragmented by special boundaries. This means that Si diffusion in annealed sample may not be reduced during brazing. The results also indicate that the modified microstructure of the core, with coarse grains distributed parallel to the rolling direction and broken random boundary network by high frequency of special boundaries, would enhance the brazeability by suppressing the excess Si grain boundary （GB） diffusion from the cladding to core material.